Performance evaluation on packet loss cost of an enhanced mobile multicast service in proxy network mobility - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Abdullah, Azween (Piscataway, New Jersey, 2016)
As forecasted by recent research, mobile Internet video traffic is reaching zettabyte capacity in 2019. The fast increments and great usage boost demand in providing high internet service performance. It has become an ongoing research trend to enhance available schemes to comply such demand. The aim of this paper is to propose a new mobile multicast scheme that is able to support high usage of mobile IP traffic. The new scheme is named as route optimized context with multicast fast reroute (RCMFR). The proposed scheme improved network mobility management multicast services support. The network mobility management is known as Proxy Mobile IPv6 (PMIPv6). The high performance of the proposed scheme is evaluated mathematically. The selected parameters are service recovery time and packet loss cost. The equations for the parameters are derived from signaling flow of the proposed scheme. Base solution is taken as the benchmark, therefore results are analyzed and compared with this scheme. The strengths of the suggested scheme is emphasized using quantitative analysis. Keywords-multicast; mobile; PMIPv6.